PERANCANGAN WEBSITE DINAS PARIWISATA KOTA PALEMBANG SEBAGAI MEDIA INFORMASI DAN PROMOSI WISATA - Hesyah Mayusdila; Rusmala Santi (CV. Denasya Smart Publisher, 2026)
The rapid growth of digital technology encourages government institutions to provide effective and easily accessible information media for the public, including in the tourism sector. The Palembang City Tourism Office has carried out various promotional activities through multiple digital platforms; however, information regarding destinations, events, and tourism activities remains dispersed and is not centralized in an official portal. This condition makes it difficult for tourists to obtain complete and accurate information. Through this internship program, a prototype of a tourism website for the Palembang City Tourism Office was designed as an integrated, modern, and user-focused information and promotional medium. The study applied the Prototyping method, consisting of requirement gathering, mockup development, and prototype evaluation. The results include user interface designs for tourists—such as destination listings, detailed destination pages, events, and organizational profiles—along with an admin interface to manage website content independently. The resulting prototype is expected to serve as a reference for developing a fully functional official website that improves the effectiveness of tourism promotion in Palembang City.